2012
DOI: 10.1016/j.bbrc.2012.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Live free or die: Stretch-induced apoptosis occurs when adaptive reorientation of annulus fibrosus cells is restricted

Abstract: High matrix strains in the intervertebral disc occur during physiological motions and are amplified around structural defects in the annulus fibrosus (AF). It remains unknown if large matrix strains in the human AF result in localized cell death. This study investigated strain amplitudes and substrate conditions where AF cells were vulnerable to stretch-induced apoptosis. Human degenerated AF cells were subjected to 1Hz-cyclic tensile strains for 24 hours on uniformly collagen coated substrates and on substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…It was also observed that widespread remodeling of cytoskeletal components is primarily restricted to OAF cells in response to cyclic tensile strain, with increased F-actin turnover and increased β-actin, β-tubulin, and collagen I expression. Supporting these findings, experiments show that human AF cells reorient themselves perpendicular to the direction of applied uniaxial stretch in a fashion dependent on actin and focal adhesions, and undergo apoptosis if this reorientation is restricted using micropatterned membranes that define cell orientation under loading 156 .…”
Section: Af Cells Isolated From the Ecm Undergo Cell Morphology Changesmentioning
confidence: 71%
“…It was also observed that widespread remodeling of cytoskeletal components is primarily restricted to OAF cells in response to cyclic tensile strain, with increased F-actin turnover and increased β-actin, β-tubulin, and collagen I expression. Supporting these findings, experiments show that human AF cells reorient themselves perpendicular to the direction of applied uniaxial stretch in a fashion dependent on actin and focal adhesions, and undergo apoptosis if this reorientation is restricted using micropatterned membranes that define cell orientation under loading 156 .…”
Section: Af Cells Isolated From the Ecm Undergo Cell Morphology Changesmentioning
confidence: 71%
“…Injury to the AF leads to a number of pathological changes, including decreased IVD cellularity, upregulated matrix‐degrading enzymes, innervation, inflammation, increased growth factor production, and formation of granulation tissue . Delamination of the AF due to excessive loading increased apoptosis of outer annulocytes and it has been suggested that annulocyte apoptotic responses may be associated with excessive cell stretching of annulocytes with limited capacity to reorient and thereby minimize the strain from loading . Furthermore, aging of IVD tissues is known to induce aberrant cellular responses to injury, including cellular senescence and dysregulated signaling, and leads to the loss of biological structure and function, which may affect healing processes.…”
Section: Cellular Responses To Injurymentioning
confidence: 99%
“…3,100,101 Delamination of the AF due to excessive loading increased apoptosis of outer annulocytes and it has been suggested that annulocyte apoptotic responses may be associated with excessive cell stretching of annulocytes with limited capacity to reorient and thereby minimize the strain from loading. 102,103 Furthermore, aging of IVD tissues is known to induce aberrant cellular responses to injury, including cellular senescence and dysregulated signaling, and leads to the loss of biological structure and function, 104 which may affect healing processes. Young and old mice express similar patterns of anabolic cytokines, although differences in the degree of expression suggests different innate responsiveness as a function of age.…”
Section: Cellular Responses To Injurymentioning
confidence: 99%
“…Previous studies have also demonstrated that the cytoskeleton might play a crucial role in mechanotransduction between IVD cells and their surrounding extracellular matrix [ 24 , 25 ]. As the F-actin cytoskeleton plays such a fundamental role in mechanotransduction between the extracellular matrix and IVD cells, it is likely that rearrangement of cytoskeletal networks may promote an imbalance in IVD homoeostasis, favoring a catabolic phenotype which is characteristic of degenerative disc disease [ 26 ]. More importantly, cytoskeleton rearrangement has been observed in discs from patients with low back pain or scoliosis compared to discs from healthy subjects [ 27 ].…”
Section: Resultsmentioning
confidence: 99%